Pharmacognostical, Phytochemical and Antimicrobial Studies of Iraqi Neem Plant (Meliaazedarachta L.) - Thamer Mouhi Jasiem (Journal of Global Pharma Technology, 2018)
Objective: The aim of this study was to investigation the macroscopical and microscopical properties conducted with preliminary screening of active compounds and investigation the antibacterial activity of leaves extract. Methods: Neem leaves were collected from Al-Musiab town at 60 Km south of Baghdad .After washed the leaves were drying then extracted by Soxhlet using 90%ethanol .Pharmacognostical study was included microscopical and macroscopical examination . The phytochemical screening was done by using reagents .Antibacterial evaluation of leaves extract was done by using diffusion method. Different bacteria were used in this study were included Staphylococcus aureus, Streptococcus spp., Pseudomonas aeruginosa, Enterococcus faecalis, Klebsiela pneumonia and E. coli. Results: The results were referred to actinocytic stomata at upper and lower surface of the leaves, while the non-glandular trichome was presented at upper surface of leaves. Also the microscopical results were referred to line shape fibers. The index of upper surface was 18% while 31% of lower surface. The preliminary results of phytochemical study were revealed the presence of flavonoids and phenolic compounds only in the plant leaves. The results of antibacterial investigation were presented different activity against all type of bacteria were used in this study.Keywords: Iraqi Neem, Flavonoids, Antibacterial.